Pengaruh Variasi Temperatur Kerja Reaktor terhadap Volume Minyak Hasil Pirolisis pada Jenis Plastik PP - Arta, Izhar Adji; Suarnadwipa, I Nengah; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstract The purpose of this research is to analyze the effect of variations in reactor working temperature on the performance of the PP plastic pyrolysis system on oil volume. A total of 3 kg of PP type plastic waste was used with 3 temperature treatments, namely 300oC, 350oC and 400oC in this research. The main research material is clear plastic. The stages carried out are preparation of tools and materials, testing tools, research treatment, ending with data processing. The resulting volume of oil obtained was different for each temperature treatment given, namely 332 mL for a temperature of 300oC; 658 mL for a temperature of 350oC; 830 mL for a temperature of 400oC. Keyword s: Pyrolysis, PP plastic, oil volume, temperature